Introduction In: Fictional Practice: Magic, Narration, and the Power of Imagination - Otto, Bernd-Christian; Johannsen, Dirk; Johannsen, Dirk (Fictional Practice: Magic, Narration, and the Power of Imagination, 2021)
Fiction, so we read in a contemporary etymological dictionary, is “that which is invented or imagined in the mind” (Harper 2020a). The word goes back to old French ficcion (“dissimulation, ruse; invention, fabrication”) and from there to the Latin fictio (which implies two distinct meanings: (1) “the act of mode- ling something, of giving it a form”; and (2) “acts of pretending, supposing, or hypothesizing”: Schaffer 2012), with its verb fingere (“to shape, form, devise, feign”) which also means “to form out of clay.” Practice, in turn, goes back to old French practiser and Latin practicare, with its root meaning of “to do, to perform.” From the fifteenth century onwards, it also acquired the meaning of “to perform repeatedly to acquire skill, to learn by repeated performance” (Harper 2020